2017
DOI: 10.1161/circoutcomes.115.001493
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Specific Aggregate Biomarker Risk Score Is Associated With Burden of Coronary Artery Disease and Predicts Near-Term Risk of Myocardial Infarction and Death

Abstract: Background Inflammation, coagulation, and cell stress contribute to atherosclerosis and its adverse events. A biomarker risk score (BRS) based on the circulating levels of biomarkers C-reactive protein, fibrin degradation products, and heat shock protein-70 representing these 3 pathways was a strong predictor of future outcomes. We investigated whether soluble urokinase plasminogen activator receptor (suPAR), a marker of immune activation, is predictive of outcomes independent of the aforementioned markers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
4
19
0
Order By: Relevance
“…The association between higher baseline suPAR and allcause mortality is consistent with other studies in select patient populations, including those with cancer, infection, cardiovascular diseases, and patients with diabetes and ESKD (23)(24)(25)(26)(27). The mechanism underlying the association between suPAR and mortality requires additional study, but it does not appear to be mediated solely by classic inflammation, as associations were robust after adjustment for CRP in our study as well as others (24,27,28).…”
Section: Discussionsupporting
confidence: 90%
“…The association between higher baseline suPAR and allcause mortality is consistent with other studies in select patient populations, including those with cancer, infection, cardiovascular diseases, and patients with diabetes and ESKD (23)(24)(25)(26)(27). The mechanism underlying the association between suPAR and mortality requires additional study, but it does not appear to be mediated solely by classic inflammation, as associations were robust after adjustment for CRP in our study as well as others (24,27,28).…”
Section: Discussionsupporting
confidence: 90%
“…However, the association between suPAR and the risk of CAD in young Chinese patients is independent of hs-CRP levels. This is in agreement with a previous report by Ghasemzedah et al who showed that suPAR, hs-CRP, fibrin degradation product, and heat shock protein-70 are independent risk factors for CAD [ 25 ]. Lyngbaek et al have shown that CRP is positively associated with anthropometric measures, such as BMI and waist circumference, whereas suPAR is linked to endothelial dysfunction and atherosclerosis [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is the first study of which we are aware comparing suPAR with CAC for association with all‐cause mortality. We and others have previously reported that suPAR levels are predictive of outcomes independent from traditional risk factors and add incremental benefit to models adjusted for biomarkers including hs‐CRP, raising the C‐statistic by 0.050 . Conversely, addition of hs‐CRP to fully‐adjusted models led to a change in C‐statistic in the range of 0.004 .…”
Section: Discussionmentioning
confidence: 83%
“…We and others have previously reported that suPAR levels are predictive of outcomes independent from traditional risk factors and add incremental benefit to models adjusted for biomarkers including hs-CRP, raising the C-statistic by 0.050. [11][12][13]17,31 Conversely, addition of hs-CRP to fullyadjusted models led to a change in C-statistic in the range of 0.004. 32 In the present AA-DHS analysis, neither hs-CRP or CAC were independent predictors of all-cause mortality or improved risk discrimination after adjusting for known clinical characteristics such as smoking, insulin use, and kidney function, findings that contrast with previously reported associations.…”
Section: Discussionmentioning
confidence: 99%